Understanding the Impact of Translingual Discrimination on Migrants’ Linguistic Integration and Emotional Wellbeing in Australia - Dryden, Stephanie Kate (Curtin University, 2024)
This thesis seeks to foster linguistic integration for transnational migrants in Australia, by investigating how translingual discrimination may influence its process. Drawing on the methodology of linguistic and digital ethnography with 50 participants, this thesis seeks to expand the concept of translingual discrimination in two ways: 1. How translingual discrimination is linked to migrants’ linguistic integration in Australia, and 2. How translingual discrimination affects the emotional wellbeing of migrants in Australia.